2022
DOI: 10.3390/nu14204278
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of Gut Microbiota in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a malignant pulmonary vascular disease characterized by increased pulmonary vascular resistance, pulmonary vasoconstriction, and right ventricular hypertrophy. Recent developments in genomics and metabolomics have gradually revealed the roles of the gut microbiota (GM) and its metabolites in cardiovascular diseases. Accumulating evidence reveals that the GM plays important roles in the occurrence and development of PAH. Gut microbiota dysbiosis directly increases the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…PHGG administration prevented PAH development in Su/Hx rats. Our previous study demonstrated that modifying the gut microbiota using antibiotics suppressed the development of pulmonary hypertension in Su/Hx rats, 17 indicating that gut dysbiosis can play a causal role in PAH development, and restoring the gut microbiota may be a new therapeutic option for PAH 3 . However, long‐term antibiotic treatment can harm patients and does not appear to be a prebiotic agent applicable in clinical situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PHGG administration prevented PAH development in Su/Hx rats. Our previous study demonstrated that modifying the gut microbiota using antibiotics suppressed the development of pulmonary hypertension in Su/Hx rats, 17 indicating that gut dysbiosis can play a causal role in PAH development, and restoring the gut microbiota may be a new therapeutic option for PAH 3 . However, long‐term antibiotic treatment can harm patients and does not appear to be a prebiotic agent applicable in clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is an ecological community of symbiotic microorganisms that play an important role in producing vitamins and maintaining gut barrier functions and the immune system 3 . Abnormal alterations, known as gut dysbiosis, are related to the development of cardiovascular diseases 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary arterial hypertension (PAH) is a vascular disease characterized by small pulmonary arteries remodeling, elevated pulmonary artery pressure and right ventricular hypertrophy [ 53 , 54 ]. PAH is a form of PH and is largely influenced by iron metabolism [ 55 ].…”
Section: Iron Metabolism Ferroptosis and Cardiovascular Diseasesmentioning
confidence: 99%
“…In systemic lupus erythematosus patients with PAH, lipopolysaccharide (LPS)-induced pyroptosis contributes to defective BMPRII (bone morphogenetic protein receptor type 2) signaling, which has a central role in PAH pathogenesis [ 13 ]. LPS is a component of the bacterial cell wall that triggers activation of toll-like receptors (TLRs), mainly TLR4, and the subsequent activation of pro-inflammatory signaling pathways, such as NF-κB, which drives inflammatory cytokine expression (e.g., IL-6), with many cytokines participating in the pulmonary vascular remodeling through perivascular inflammation [ 14 ]. An increase in serum LPS level, thought to be related to the gut dysbiosis commonly observed in PAH patients, has been noted in preclinical animal models of PAH, such as monocrotaline-treated rats, as well as in various forms of PAH, including IPAH, HPAH, PAH, and the aforementioned PAH due to SLE [ 13 , 14 , 15 ].…”
Section: Current Understanding Of Pah Pathogenesismentioning
confidence: 99%